Interleukin 1 alpha and beta production by cells isolated from membranes around aseptically loose total joint replacements - Westacott, C I; Taylor, G; Atkins, R; Elson, C (Annals of the rheumatic diseases, 1992)
Aseptic loosening of joint prostheses is accompanied by local osteolysis. To determine whether local production of interleukin 1 might contribute to such lysis, the number of interleukin 1 secreting cells in the pseudosynovial membrane surrounding prostheses was measured. Interleukin 1 alpha and beta secreting cells were identified by ELISPOT, a sensitive cytokine secreting assay. The proportion of interleukin 1 beta secreting cells in pseudosynovial membrane was comparable with the proportion occurring in the synovium of patients with rheumatoid arthritis and higher than that in normal subjects and patients with osteoarthritis. The proportion of interleukin 1 alpha producing cells was higher in pseudosynovial membrane than in diseased synovium. Overall, higher numbers of interleukin 1 beta than interleukin 1 alpha secreting cells were detected. A correlation was observed between the number of cells in pseudosynovial membrane producing interleukin 1 beta and those producing interleukin 1 alpha. When divided into area of origin, tissue samples from the femoral area contained a higher proportion of interleukin 1 beta producing cells than tissue in the acetabular or capsular regions, though due to variance within each group this difference did not reach significance.